Enhanced conversion efficiency in dye-sensitized solar cells based on ZnO bifunctional nanoflowers loaded with gold nanoparticles - Dhas, Vivek V.; Muduli, Subas; Lee, Wonjoo; Han, Sung-Hwan; Ogale, Satishchandra B. (Applied Physics Letters, 2008)
The ZnO nanoflowers loaded with gold (Au) nanoparticles (NPs) are synthesized by a hydrothermal route using mixed precursors and controlled conditions. The dye-sensitized solar cells based on the ZnO nanoflowers with Au NPs show power conversion efficiency of 2.5%, which is considerably higher than that of ZnO nanoflowers without Au NPs. Detailed characterizations are performed, presented, and discussed.
Keywords: crystal growth from solution; Gold; II-VI semiconductors; Nanocomposites; Nanoparticles; solar cells; wide band gap semiconductors; zinc compounds

Electronic manifestation of cation-vacancy-induced magnetic moments in a transparent oxide semiconductor: anatase Nb:TiO2 - Zhang, Shixiong; Ogale, Satishchandra B.; Yu, Weiqiang; Gao, Xingyu; Liu, Tao; Ghosh, Saurabh; Das, Gour P.; Wee, Andrew T. S.; Greene, Richard L.; Venkatesan, Thirumalai (Advanced Materials, 2009)
Nb-doped anatase TiO2 thin films grown by pulsed-laser deposition show Kondo scattering in elctronic-transport measurements, providing evidence for the formation of magnetic moments. The origin of magnetism is attributed to cation (Ti) vacancies, confirmed by X-ray absorption spectroscopy and first-principle calculations. The Ti vacancies are controlled by oxygen partial pressure during growth.

Enhanced nonvolatile resistive switching in dilutely cobalt doped TiO2 - Bogle, Kashinath A.; Bachhav, Mukesh N.; Deo, Meenal S.; Valanoor, Nagarajan; Ogale, Satishchandra B. (Applied Physics Letters, 2009)
Incorporation of dilute concentration of dopant having a valence state different than that of the host cation enables controlled incorporation proximity vacancy defects for local charge balance. Since nonvolatile resistive switching is a phenomenon tied to such defects, it can be expected to be influenced by dilute doping. In this work, we demonstrate that enhanced nonvolatile resistive switching is realized in dilutely cobalt doped TiO2 films grown at room temperature. We provide essential characterizations and analyses. We suggest that the oxygen vacancies in the proximity of immobile dopants provide well distributed anchors for the development of systematic filamentary tracks.
Keywords: cobalt; Doping; magnetic switching; random-access storage; titanium compounds; vacancies (crystal); valency

Enhanced DSSC performance with high surface area thin anatase TiO2 nanoleaves - Dhas, Vivek V.; Muduli, Subas; Agarkar, Shruti A.; Rana, Abhimanyu; Hannoyer, Beatrice; Banerjee, Rahul; Ogale, Satishchandra B. (Solar Energy, 2011)
Thin anatase TiO2 nanoleaves (NLs) with high surface area (similar to 93 m(2)/g) are synthesized by hydrothermal route and dye-sensitized solar cells (DSSC) made using such NLs are compared with those made with hydro-thermally synthesized TiO2 nanoparticles and the Degussa P25 powder. The NLs-based DSSCs show increment of 16% and 24% in the total conversion efficiency over the cells made with NPs and P25 respectively. Interestingly, the highest increment in the conversion efficiency (similar to 35%) is achieved for cells made using a 50:50 (wt/wt) mixture of NLs and NPs. In this case the dye loading is found to be >50% higher than the case of NP films. Moreover the DC resistance of diffusion of I-3(-) in electrolyte (as revealed by the electrochemical impedance spectroscopy) is substantially lower than the NP film case, other cell parameters being nominally comparable. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Dye-sensitized solar cells; Electrochemical impedance spectroscopy; hydrothermal

Evidence of lateral heat transfer during laser assisted atom probe tomography analysis of large band gap materials - Bachhav, Mukesh N.; Danoix, R.; Vurpillot, F.; Hannoyer, Beatrice; Ogale, Satishchandra B.; Danoix, F. (Applied Physics Letters, 2011)
Investigation of wustite (FeO), iron (Fe), and silicon (Si) specimens by infrared laser assisted three dimensional atom probe tomography shows evidence of confined surface absorption of the laser energy as the mechanism of laser assisted field evaporation for high band gap materials. The absorption region is shown to be located on the laser illumination side, close to the specimen apex. A simple model based on thermal diffusivity and spatial extent of the absorption region is derived and applied to the experimental results. The values of thermal diffusivity thus obtained are in good agreement with the published data. (C) 2011 American Institute of Physics. [doi:10.1063/1.3622647]

Epitaxial magnetic oxide nanocrystals via phase decomposition of bismuth perovskite precursors - Bogle, Kashinath A.; Cheung, Jeffrey; Chen, Yong-Lun; Liao, Sheng-Chieh; Lai, Chih-Hung; Chu, Ying-Hao; Gregg, John M.; Ogale, Satishchandra B.; Valanoor, Nagarajan (Advanced Functional Materials, 2012)
The phase instability of bismuth perovskite (BiMO3), where M is a ferromagnetic cation, is exploited to create self-assembled magnetic oxide nanocrystal arrays on oxide supports. Conditions during pulsed laser deposition are tuned so as to induce complete breakdown of the perovskite precursor into bismuth oxide (Bi2O3) and metal oxide (M-Ox) pockets. Subsequent cooling in vacuum volatizes the Bi2O3 leaving behind an array of monodisperse nanocrystals. In situ reflective high energy electron diffraction beam is exploited to monitor the synthesis in real-time. Analysis of the patterns confirms the phase separation and volatization process. Successful synthesis of M-Ox, where M = Mn, Fe, Co, and Cr, is shown using this template-free facile approach. Detailed magnetic characterization of nanocrystals is carried out to reveal the functionalities such as magnetic anisotropy as well as larger than bulk moments, as expected in these oxide nanostructures.
Keywords: Bi2O3 evaporation; bismuth perovskites; epitaxial nanostructures; magnetic oxides; phase separation

Enhanced catalytic activity of polyethylenedioxythiophene towards tri-iodide reduction in DSSCs via 1-dimensional alignment using hollow carbon nanofibers - Anothumakkool, Bihag; Game, Onkar S.; Bhange, Siddheshwar N.; Kumari, Tanya; Ogale, Satishchandra B.; Kurungot, Sreekumar (Nanoscale, 2014)
Here, we report a highly conducting 1-dimensionally (1-D) aligned polyethylenedioxythiophene (PEDOT) along the inner and outer surfaces of a hollow carbon nanofiber (CNF) and its application as a counter electrode in a dye sensitized solar cell (DSSC). The hybrid material (CP-25) displays a conversion efficiency of 7.16% compared to 7.30% for the standard Pt counter electrode, 4.48% for bulk PEDOT and 5.56% for CNF. The enhanced conversion efficiency of CP-25 is attributed to the accomplishment of high conductivity and surface area of PEDOT through the 1-D alignment compared to its bulk counterpart. Reduced charge transfer resistance and high conductivity of CP-25 could be proven by cyclic voltammetry, impedance analysis and Tafel experiments. Further, through a long-term stability test involving efficiency profiling for 20 days, it is observed that CP-25 possesses excellent durability compared to the bulk PEDOT.

Enhancing efficiency of perovskite solar cell via surface microstructuring: superior grain growth and light harvesting effect - Tathavadekar, Mukta C.; Agarkar, Shruti A.; Game, Onkar S.; Bansode, Umesh P.; Kulkarni, Sneha A.; Mhaisalkar, Subodh G.; Ogale, Satishchandra B. (Solar Energy, 2015)
We have introduced a novel approach to enhance the perovskite solar cell efficiency by controlling the grain growth and light harvesting properties of perovskite crystallites. Instead of using a mesoporous TiO2 layer, we have modified the surface microstructuring of the TiO2 film by dispensing nano assembled TiO2 submicron structures (nanobeads, NBs) on TiO2 compact layer. With this new approach solar cell efficiency was improved significantly through an increase in both J(sc) and V-oc. This high efficiency is attributed to crystallite size of the perovskite phase. These also act as light scattering centers giving higher current density and reduced recombination effects giving higher open circuit voltage. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Grain growth; Light harvesting; Perovskite solar cells; TiO2 nanobeads